Altova Enterprise Suite 2005 effective, powerful and useful. - Barbash, Brian
XML development is a term that can mean many things to many different people. For some, it is the modeling and creation of XML Schemas and instance documents used to exchange data. Others see it as a part of the larger effort of developing Web services. Still others view it as a means to transform and integrate systems whose data structures and definitions are proprietary. All of these types of development require various skills and tools.